Bovine tuberculosis in domestic pigs: Genotyping and distribution of isolates in Argentina - Barandiaran, Soledad (2015)
Bovine tuberculosis is caused by Mycobacterium bovis and affects primarily cattle, among many other mammal species. In this study, 250 isolates of M. bovis collected from pigs slaughtered in Argentina were typed by spoligotyping. Over half of the isolates (66%) grouped into two spoligotypes. Moreover, SB0140 was the most frequent spoligotype detected in the three performed samplings. In addition, 195 isolates were typed through variable number of tandem repeats (VNTR) by selecting 7 loci (MIRU 16–26–31 and ETR A–B–C–D). The relationship among the patterns was performed using a goeBURST algorithm and the main clonal complexes grouped 110 isolates (56%). Although pigs shared genotypes with cattle (n = 21), some patterns were detected only in pigs (n = 14). These findings suggest the pig as a source of M. bovis infection to cattle.